POLA PENGELOLAAN EKOWISATA BERBASIS KOMUNITAS DI TAMAN NASIONAL GUNUNG HALIMUN SALAK - Keliwar, Said (JURNAL NASIONAL PARIWISATA, 2013)
The purpose of this study was to determine the mechanism of community-based ecotourism management and community development in the village Cipta Gelar Mountain Salak National Park in the management of ecotourism. The study uses survey methodology is supported by in-depth interviews as well as field observations associated with ecotourism components and mechanisms, such as tourist attractions, tourist facilities, accessibility, promotion, partnership and empowerment.Community based ecotourism management scheme in village Cipta Gelar has natural and cultural tourist attractions are diverse and unique, such as: mountain scenery, rice fields, flora and fauna, the pattern of society still holds strong ancestral traditions, such as ceremonial epidemic, tradition of farming, building a house, the architecture of the house, hand souvenirs, making it all the palm sugar into tourism products, but its implementation has not been able to run optimally. Tourist facilities available are quite good. The road network is not good enough and not yet available.Community empowerment programs implemented have not done intensively and most especially in the management of community-based ecotourism so not many tangible economic benefits for the community.